Evaluation of Information Systems on the SIMDAPRO using the Unfield Theory of Acceptance and Use of Technology (UTAUT) Method - Hasbiallah, Muhammad Jidan; Ibrahim, Ali; Indah, Dwi Rosa; Seprina, Iin; Firnando, Ricy (Asosiasi Doktor Sistem Informasi Indonesia, 2024)
The Management Information System for Housing Profile Data and Settlement Areas (SIMDAPRO) is a web-based system managed by Department Housing settlement Areas South Sumatra Province (DISPERKIM).. This system is integrated and unified, thus accelerating and improving the process of proposing assistance from the South Sumatra Provincial Government. Additionally, it facilitates related parties in verifying proposals. To analyse the factors influencing to understand how people accept and use the information technology, This study employs the UTAUT model, comprising four primary constructs: the first one is performance expectancy, and the next is the second effort expectancy, and the next one is the third social influence, and the next one is the fourth facilitating conditions. It aims to examine how these constructs influence the behavioral intention of (SIMDAPRO) application users in South Sumatra Province. The research approach is quantitative accompanied by a survey method. The research sample consists of 34 respondents who were chosen through using purposive sampling. Data collection techniques include validation, questionnaires, and observation. with instrument tests conducted for validity and reliability. The findings reveal that all four constructs the first one is performance expectancy, and the next is the second effort expectancy, and the next one is the third social influence, and the next one is the fourth facilitating conditions. significantly and positively impact the behavioral intention of SIMDAPRO application users in South Sumatra Province.